(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA) farm, Mymensingh to study the effect of rhizobial inoculant (biofertilizer) on the the yield and yield contributing characters of mungbean cultivars. Experimental treatments included two varieties of mungbean namely Binamoog5 and Binamoog7 and six inoculant treatments namely control(I0), Bradyrhizobium Inoculant(I), Inoculant+P, NPK, Inoculant+PK+B and Inoculant+PK+CD. Inoculantion+PK+B obtained the highest grain yield of mungbean (1.49 t ha-1) while Inoculantion+PK+CD showed the highest straw yield. NPK application showed significantly higher grain and straw yield over uninoculated control and parallel to inoculation but statistically inferior to I+PK+CD in respect of grain yield. Inoculantion+PK+CD or Inoculantion+PK+B may be recommended for summer mungbean production where I+PK+CD is preferable. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11584 J. Environ. Sci. & Natural Resources, 5(1): 211 - 215, 2012